Exhausting Silence: Emotional Costs of Withholding Complaints. (February 2015) - Liu, Esther; Roloff, Michael E.
Abstract Individuals often withhold relational complaints rather than disclosing them. Withholding relational complaints not only impacts relationships but can also have implications for individual behaviors and emotions. This study examined cognitive activities and behavioral aggression involved in withholding relational complaints and the emotional impact of withholding. The student‐based sample consisted of 395 participants who completed a survey about emotion regulation responses (rumination and reappraisal) to an irritating experience, passive aggressive behaviors (silent treatment and stonewalling), and emotional exhaustion. The findings provide evidence for posited mediated relationships between rumination and emotional exhaustion through passive aggressive behaviors. Implications for managing challenging emotional situations and examining complaint withholding in the workplace are discussed.